A legal study on the issuance of court documents by substituted service through Social Networking Sites (SNS) in Malaysia / Farah Nadira Abdul Ghani, Nurul Ain Ibrahim and Noor Shakinah Samian - Abdul Ghani, Farah Nadira; Ibrahim, Nurul Ain; Samian, Shakinah (2011)
It cannot be denied that Malaysia is concerned with the Information Communication Technology (ICT) development. The syariah court of Malaysia has moved to set up the E-Syariah case management structure. Meanwhile, in civil court, E-Filing has been introduced recently. A Legal Study On The Issuance Of Court Documents By Substituted Services Through Social Networking Sites (SNS) In Malaysia is a research focusing on recommendations of the use of social networking sites in serving court documents by the plaintiff in a civil litigation. Substituted service through social networking sites is a topic which touches on the possibility of the acceptance of the advancement of technology in serving court docuemnts relating to the civil procedure in Malaysia. More importantly, the research paper will lay out the authorities of other countries that has already accepted social networking sites as part of the modes of service of court documents in the civil procedure. Chapter Two of the research deals with the definition of SNS, the examples of SNS, the developments of SNS, the advantages and disadvantages of SNS, and also the popularity of SNS. Secondly, Chapter Three focuses on the service of writ and the substituted service currenltly practiced in Malaysia. It also looks into the conventional modes of substituted service and relevant cases dealing with failure of the existing conventional modes of substituted services. Chapter Four examines the development of substituted service through social networking sites (SNS) in Australia, United Kingdom and New Zealand where each and every jurisdiction has its own specific rules on how the service of court documents via SNS should be accomplished. Finally, Chapter Five sets out the conclusion and recommendations for the issuance of court documents by substituted services through social networking sites (SNS) in Malaysia.